2017
DOI: 10.1136/jclinpath-2016-204230
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear survivin expression correlates with endoglin-assessed microvascularisation in laryngeal carcinoma

Abstract: Survivin-targeting strategies to enhance tumour cell response to apoptosis and inhibit tumour growth should receive more attention with a view to developing agents for use in multimodality advanced LSCC treatment, or combined with conventional chemotherapy. Given the present preliminary evidence in LSCC, survivin targeting should also be further investigated for anti-angiogenic purposes, to reduce tumour blood flow and induce cancer necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Univariate Cox regression analysis identified high nuclear Survivin expression, plus key clinicopathologic factors, including histological grade (G3‐4), vessel invasion, N1 stage, and without the ACT, as predictors of poor prognosis. The survival results support the above ones and those by Xie et al Previously, the positive associations of nuclear Survivin and aggressive phenotypes, such as cell proliferation and microvascular density (MVD) and/or poor prognosis, were also revealed by many papers in many malignant tumors . In vitro investigations showed that nuclear Survivin play its oncogenic role via many molecular mechanisms, such as abrogation of cell‐cycle checkpoints, an increase of DNA repair capacity, and activation of nuclear factor κB (NF‐κB) p65, in cancer cells .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Univariate Cox regression analysis identified high nuclear Survivin expression, plus key clinicopathologic factors, including histological grade (G3‐4), vessel invasion, N1 stage, and without the ACT, as predictors of poor prognosis. The survival results support the above ones and those by Xie et al Previously, the positive associations of nuclear Survivin and aggressive phenotypes, such as cell proliferation and microvascular density (MVD) and/or poor prognosis, were also revealed by many papers in many malignant tumors . In vitro investigations showed that nuclear Survivin play its oncogenic role via many molecular mechanisms, such as abrogation of cell‐cycle checkpoints, an increase of DNA repair capacity, and activation of nuclear factor κB (NF‐κB) p65, in cancer cells .…”
Section: Discussionsupporting
confidence: 83%
“…The survival results support the above ones and those by Xie et al 26 Previously, the positive associations of nuclear Survivin and aggressive phenotypes, such as cell proliferation and microvascular density (MVD) and/or poor prognosis, were also revealed by many papers in many malignant tumors. [34][35][36][37] In vitro investigations showed that nuclear Survivin play its oncogenic role via many molecular mechanisms, such as abrogation of cell-cycle checkpoints, an increase of DNA repair capacity, and activation of F I G U R E 3 Prognostic value of nuclear Survivin expression in subgroups of pancreatic ductal adenocarcinoma. A, Male patients (log-rank test; P = 0.0129); B, nondiabetic patients (log-rank test; P = 0.0344); C, patients with head-located tumors (log-rank test; P = 0.0264); D, patients with G1-2 tumors (log-rank test; P = 0.0206).…”
Section: Univariate Cox Regression Analysis Identified High Nuclear Smentioning
confidence: 99%
“…In our study endoglin was one of the proteins affected by RT in HNSCC patients. Functionally endoglin is involved in angiogenesis and intratumoral endoglin level is an important marker of tumor angiogenesis and neovascularization process [33,34]. Both intratumoral endoglin expression and circulating endoglin levels were correlated with therapy response and long-term prognosis [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…The main strength of our investigation lies in the homogeneity of the patient population since: (i) all patients underwent surgery; (ii) their surgical treatment was performed consecutively by the same team; (iii) only squamous cell carcinomas located in the larynx were considered; (iv) for each case, both biopsies and surgical specimens were assessed and compared; (v) both CD105 and CD31 were used to assess MVD; (vi) clinical-radiological follow-up criteria were defined; (vii) a tailored multivariable statistical model was used to analyze the variables potentially predictive of DFS. In addition, over the course of about 15 years [23], the pathologists in our research group have gained plenty of experience of assessing MVD from the immunohistochemical expression of CD105 in head and neck malignancies [24], also in association with oncogenes [25], or tumor suppressors [26]. The main weaknesses of our study concern the retrospective setting and the limited number of cases considered.…”
Section: Discussionmentioning
confidence: 99%